SPE/DOE Enhanced Oil Recovery Symposium 1990
DOI: 10.2118/20245-ms
|View full text |Cite
|
Sign up to set email alerts
|

Foams as Mobility Control Agents for Oil Recovery by Gas Displacement

Abstract: Experimental studies were conducted to facilitate understanding of the behavior of foam flow and its application in gas flooding processes. This paper presents the results of studies that involved: (1) foam flow behavior in smooth capillary tubes and packed glass tubes; (2) effects of changes in injection rates on foam performance; (3) effects of foams on unsteady state gas-liquid relative permeabilities; and (4) effects of foams on improving gas sweep efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Results show that foam was preferentially generated in the more permeable plug and could divert CO 2 towards the less permeable plug. Llave et al (1990) showed similar results with parallel plugs with permeability ratio of 4.6. Field trials have also been conducted with some success.…”
Section: Introductionsupporting
confidence: 69%
“…Results show that foam was preferentially generated in the more permeable plug and could divert CO 2 towards the less permeable plug. Llave et al (1990) showed similar results with parallel plugs with permeability ratio of 4.6. Field trials have also been conducted with some success.…”
Section: Introductionsupporting
confidence: 69%
“…Diversion of gas into lower-permeability layers using foams has previously been reported [see, for example, Casteel and Djabbarah (1988), Llave et al (1990), Zerhboub et al (1994), and Nguyen et al (2003)]. This may be important for fractured systems, where a very large permeability contrast exists and crossflow between the zones occurs (Bertin et al 1999).…”
Section: Introductionmentioning
confidence: 96%
“…Permeability contrasts have significant effects during EOR projects in which the injected EOR agent tends to flow within the fracture network rather than sweep the oil-saturated matrix blocks (Manrique et al 2007). In addition, oil is retained in the rock matrix by capillary forces in oil-wet formations (Hirasaki and Zhang 2004), but can be produced by either reducing the interfacial tension (IFT) or changing the matrix wettability using additives in the water including surfactants (Seethepalli et al 2004) or sulfate (Austad and Standnes 2003).…”
Section: Introductionmentioning
confidence: 99%